KELUARGA BERENCANA DALAM RANGKA MEWUJUDKAN KELUARGA SAKINAH DI MUNGKID, MAGELANG, JAWA TENGAH - Setyaningsih, Yunika Isma; Ibrahim, Malik (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
In 1970 the family planning program (KB) became popular, then disseminated to various regions in Indonesia. When the demand is still relatively small due to stumble to the problem of whether its allowed or not allowed to run this program by the law of Islam. In addition, Lack of public awareness of KB regarding the usefulness or importance of family planning. This paper presents an overview of the implementation of KB from Islamic law perspective in the village of Ngrajek in order to consummate the harmonious family. Basically, the determining or primary factor of the realization of the harmonious family is the awareness and responsibility of husband and wife in their functions and roles, as well as the rights and obligations of conjugal supported by the family economy. Thus, the use of KB contraceptives is only a secondary factor. Therefore, harmonious family phasing criteria set by the Ministry of Religion, highlights from the viewpoint of religious life and the family economy. Implementation of KB on the family in accordance with Islamic law, because their motivation in family planning(KB) Program is for the welfare of the family and to adjust the spacing of birth, and do not cause madlarat for each family. [Pada tahun 1970 Keluarga Berencana mulai populer, kemudian disosialisasikan ke berbagai daerah di Indonesia. Saat itu peminatnya masih relatif sedikit karena terbentur dengan masalah boleh atau tidaknya ber-KB menurut agama. Selain itu, kesadaran masyarakat juga masih kurang mengenai kegunaan atau pentingnya ber-KB. Tulisan ini memaparkan pandangan Hukum Islam mengenai pelaksanaan KB di Desa Ngrajek dalam rangka mewujudkan keluarga sakinah. Pada dasarnya, penentu atau faktor primer terwujudnya keluarga sakinah adalah kesadaran dan tanggung jawab suami isteri dalam menjalankan peran dan fungsinya, serta menjalankan hak dan kewajiban suami isteri yang didukung oleh perekonomian keluarga. Jadi, memakai alat kontrasepsi KB hanya faktor sekunder saja. Sebab, kriteria pentahapan keluarga sakinah yang ditetapkan oleh Kementerian Agama banyak menyoroti dari sudut pandang kehidupan beragama dan perekonomian keluarga. Pelaksanaan KB pada keluarga telah sesuai dengan syariat Islam, karena motivasi mereka dalam ber-KB adalah untuk mewujudkan kesejahteraan keluarga dan untuk mengatur jarak kelahiran, serta tidak menimbulkan madlarat bagi masing-masing keluarganya.]